Translational materials research - From laboratory to product: A 1200 F cylindrical supercapacitor from petroleum coke derived activated carbon sheets. (25th November 2022) - Nanaji, Katchala; Nirogi, Aamani; Srinivas, Pavan; Anandan, Srinivasan; Vijay, R.; Bathe, Ravi Nathuram; Pramanik, M.; Narayan, K.; Ravi, B.; Rao, Tata N.
Abstract: Cylindrical supercapacitors are ideal energy storage devices for electric vehicle applications because of their safety, high power, and capacitance. In this regard, synthesis and utilization of activated carbon materials in supercapacitors for commercial usage is the need of the hour. Many researchers have reported the synthesis of carbon-based materials for supercapacitor application. However, the studies and application of such materials are limited to laboratory coin-cell level testing. In this work, for the first time, we have not only synthesized activated carbon sheets with a surface area of 2394 m 2 /g from petroleum coke but also demonstrated the commercial applicability of petroleum coke derived activated carbon sheets by fabricating a cylindrical supercapacitor with the specifications of 2.7 V and 1200 F, and the dimension of (60 × 80 mm) (D × H). The cylindrical supercapacitor exhibited a high capacitance of 1202 F with a stored energy of 1.22 Wh and a gravimetric energy density of 5.05 Wh/Kg. Also, the indigenous cylindrical device was diffusely compared with a commercially available supercapacitor of similar size, and the fabricated supercapacitor in this work reveals a great potential in terms of promising electrochemical properties for commercial applicability. The results also demonstrate that the petroleum coke carbon-based supercapacitor developed in this work can be used as an alternative to the commercial coconut charcoal carbon-based supercapacitor due to the inexpensive petroleum coke with rich carbon content. Graphical abstract: Unlabelled Image Highlights: Conversion of Petroleum Coke waste into porous graphene carbon sheets at a low temperature of 900 oC. The material exhibits a graphene sheet-like morphology with an interlayer d-spacing of 0.34 nm and ID /IG of 0.89. Demonstration of the commercial applicability of the graphene sheets by fabricating a cylindrical supercapacitor. The fabricated supercapacitor exhibits a high capacitance of 1200 Farads with a stored energy of 1.22 Wh. Can be an alternative to the commercial coconut charcoal carbon-based supercapacitor.